Global DevOps Market Dynamics and Workforce Analysis - Oksana Vasylenko; Kateryna Shulakova; Liliia Bodnar; Eduard Siemens; Roman Tsarov; Oleksandr Vudvud (Proceedings of the International Conference on Applied Innovations in IT, 2025)
This study delivers a comprehensive analysis of the global DevOps market, dissecting its growth trajectory, regional adoption variations, and salary dynamics as observed in 2024. Synthesizing data from recent industry surveys and market reports, the research evaluates the market's current valuation, forecasts projected growth rates, and identifies the key factors driving regional disparities in DevOps implementation. Beyond mere market metrics, this study delves into the intricacies of salary ranges for DevOps engineers worldwide, illuminating the significant impact of both market demand and regional economic conditions on compensation structures. Further enriching the analysis, the paper explores the demographic and firmographic characteristics of IT professionals, offering critical insights into the composition of the workforce, the distribution of roles within organizations, and the strategic implications for talent management. By integrating quantitative market data with qualitative insights into workforce demographics, this research aims to equip IT professionals, business leaders, and policy-makers with actionable intelligence, enabling them to effectively navigate the evolving DevOps environment and make informed strategic decisions that align with current and future market demands. This study not only highlights the current state of the DevOps market but also provides a forward-looking perspective, emphasizing the importance of adapting to the rapid changes in technology and workforce dynamics.